2021
DOI: 10.1126/sciadv.abc7358
|View full text |Cite
|
Sign up to set email alerts
|

Warming homogenizes apparent temperature sensitivity of ecosystem respiration

Abstract: Warming-induced carbon loss through terrestrial ecosystem respiration (Re) is likely getting stronger in high latitudes and cold regions because of the more rapid warming and higher temperature sensitivity of Re (Q10). However, it is not known whether the spatial relationship between Q10 and temperature also holds temporally under a future warmer climate. Here, we analyzed apparent Q10 values derived from multiyear observations at 74 FLUXNET sites spanning diverse climates and biomes. We found warming-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 134 publications
0
8
2
Order By: Relevance
“…Currently, many research studies have focused on the response of vegetation phenology to specific climate factors, including temperature, precipitation, and shortwave radiation. The results indicated that interaction between temperature, shortwave radiation, and water has caused various impacts on vegetation activities in different regions [16][17][18]. For example, the SOS arrived 2.5 days earlier, and the EOS was delayed by 1 day for every 1 • C increase in the temperature across 19 European countries [19].…”
Section: Introductionmentioning
confidence: 98%
“…Currently, many research studies have focused on the response of vegetation phenology to specific climate factors, including temperature, precipitation, and shortwave radiation. The results indicated that interaction between temperature, shortwave radiation, and water has caused various impacts on vegetation activities in different regions [16][17][18]. For example, the SOS arrived 2.5 days earlier, and the EOS was delayed by 1 day for every 1 • C increase in the temperature across 19 European countries [19].…”
Section: Introductionmentioning
confidence: 98%
“…Our models implicitly assumed an increasing exponential relationship between temperature and respiration. The temperature sensitivity of respiration (Q 10 ) across ecosystems can vary (usually around 2-5) (Chen and Tian, 2005;Wang et al, 2006;Bond-Lamberty and Thomson, 2010) and is generally expected to be greater than 1, but the Q 10 value may decrease as soils warm (Niu et al, 2021). Some degree of additional variability is expected when considering the biochemical or thermodynamic foundations of respiration (Lloyd and Taylor, 1994;Ito et al, 2015), the methodological approach used to measure soil respiration (Ribeiro-Kumara et al, 2020b), or variation in the soil organic matter supply (Davidson et al, 2006).…”
Section: Evaluation Of Parameter Estimation Approachesmentioning
confidence: 99%
“…Improving the structural representation of microbial respiration in earth system models (e.g. accounting for microbial acclimation to non-equilibrium temperature changes, Zobitz et al (2008); Wieder et al (2013); Wang et al (2021)), when appropriately benchmarked with data, may reduce uncertainties in the turnover and stabilization of soil carbon (Wieder et al, 2013;Sihi et al, 2016). However, there are two main challenges to developing and evaluating more complicated soil process models.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of carbon neutrality, greater attention is being paid to the spatiotemporal variation of net carbon uptake, which has not yet been systematically evaluated. In addition, the respiratory sensitivity of the ecosystem on the plateau will decrease significantly as the climate warms [24], but the extent of the decrease is unclear. Therefore, it is necessary to systematically evaluate the carbon budget and its climatic driving mechanism in the alpine grassland on the QTP (AG QTP ).…”
Section: Introductionmentioning
confidence: 99%